On some fučík type problem with cubic nonlinearity - Sergejeva, N. (Mathematical Modelling and Analysis, 2011)
We study the second order Fučík type problem with cubic nonlinearity  and construct the Fučík spectrum for this problem. The spectrum obtained under normalization condition (otherwise problem may have continuous spectra) structurally is similar to Fučík spectra for the problem   with the same boundary conditions.